Översättningsmodeller i en ordbok? En liten användarundersökning - Martola, Nina (Nordiske Studier i Leksikografi, 2001)
In the new Finnish-Swedish bilingual dictionary published in 1997 there are models for how to translate certain types of Finnish words. The models are part of the front matter and from the entries there are references to the models. The word types in question are derivatives that have no equivalents at all in Swedish, or the equivalents of which cannot be constituents of the same type of syntactical constructions as the Finnish words. In order to find out whether this concept seems to work I have carried out user research where students were asked to translate sentences containing these types of construcions whith the help of our models. A control group got another text about translating instead. The test persons were also asked to evaluate the models. Even if the differences between the two groups were not very big, the result was not entirely discouraging.